Anti‐IFN‐α/‐ω neutralizing antibodies from COVID‐19 patients correlate with downregulation of IFN response and laboratory biomarkers of disease severity. Issue 7 (28th April 2022) - Frasca, Federica; Scordio, Mirko; Santinelli, Letizia; Gabriele, Lucia; Gandini, Orietta; Criniti, Anna; Pierangeli, Alessandra; Angeloni, Antonio; Mastroianni, Claudio M.; d'Ettorre, Gabriella; Viscidi, Raphael P.; Antonelli, Guido; et al.
Abstract: A significant number of COVID‐19 patients were shown to have neutralizing antibodies (NAB) against IFN; however, NAB specificity, fluctuation over time, associations with biochemical and hematological parameters, and IFN gene expression are not well characterized. Binding antibodies (BAB) to IFN‐α/‐β were screened in COVID‐19 patients' serum. All BAB positive sera, and a subset of respiratory samples, were tested for NAB against IFN‐α/‐β/‐ω, using an antiviral bioassay. Transcript levels of IFN‐α/‐β/‐ω and IFN‐stimulated genes (ISGs) were quantified. Anti‐IFN‐I BAB were found in 61 out of 360 (17%) of patients. Among BAB positive sera, 21.3% had a high NAB titer against IFN‐α. A total of 69.2% of anti‐IFN‐α NAB sera displayed cross‐reactivity to IFN‐ω. Anti‐IFN‐I NAB persisted in all patients. NAB to IFN‐α were also detected in 3 out of 17 (17.6%) of respiratory samples. Anti‐IFN‐I NAB were higher in males ( p = 0.0017), patients admitted to the ICU ( p  < 0.0001), and patients with a fatal outcome ( p  < 0.0001). NAB were associated with higher levels of CRP, LDH, d ‐Dimer, and higher counts of hematological parameters. ISG‐mRNAs were reduced in patients with persistently NAB titer. NAB are detected in a significant proportion of severe COVID‐19. NAB positive patients presented a defective IFN response and increased levels of laboratory biomarkers of disease severity. Abstract : Autoantibodies capable of neutralizing multiple IFN‐α subtypes and IFN‐ω can be found in severe COVID‐19 patients, preferentially males. Anti‐IFN‐I neutralizing antibodies (NAB) positive patients present a defective IFN response and have raised levels of biochemical and hematological parameters predictive of severe COVID‐19.